2009
DOI: 10.1080/10934520802539830
|View full text |Cite
|
Sign up to set email alerts
|

Photo-catalytic degradation of an oil-water emulsion using the photo-fenton treatment process: Effects and statistical optimization

Abstract: The application of advanced oxidation processes (AOPs) to the treatment of an effluent contaminated with hydrocarbon oils was investigated. The AOPs conducted were Fe 2+ /H 2 O 2 (Fenton's reagent), Fe 2+ /H 2 O 2 /UV (Photo-Fenton's reagent) and UV-photolysis. These technologies utilize the very strong oxidizing power of hydroxyl radicals to oxidize organic compounds to harmless end products such as CO 2 and H 2 O. A synthetic wastewater generated by emulsifying diesel oil and water was used. This wastewater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 25 publications
3
43
0
Order By: Relevance
“…The Fenton reagent was then introduced to the solution by adding the ferrous solution (40 mg/L) and hydrogen peroxide (400 mg/L), these dosages having been determined in previous work. [10] For the experiments in which TiO 2 or ZnO were used, these reagents were added to the oil-water emulsion prior to the addition of Fenton's reagent. In the case of the experiments where the effect of the pH was examined, the pH of the emulsion was adjusted before all the reagents were added.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fenton reagent was then introduced to the solution by adding the ferrous solution (40 mg/L) and hydrogen peroxide (400 mg/L), these dosages having been determined in previous work. [10] For the experiments in which TiO 2 or ZnO were used, these reagents were added to the oil-water emulsion prior to the addition of Fenton's reagent. In the case of the experiments where the effect of the pH was examined, the pH of the emulsion was adjusted before all the reagents were added.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Previous work by the authors demonstrate the application of Fenton's and the photoFenton's reagent in the case of a diesel-oil emulsion and a real car-wash wastewater treatment and the optimization of the process parameters. [10] The application of UV/Fenton/TiO 2 has been reported extensively in the literature, though there is a scarcity of literature published in the case of oily wastewater treatment. For example, Duran and Monteagudo [11] studied the application of the UV/Fenton/TiO 2 for the mineralization of the reactive blue 4 dye using solar light as the source of the UV radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Among various AOPs, the Fenton reagent is one of the most effective methods for treating various industrial effluents including wastewater [13,14] and oily wastewater [15]. Previous work by the authors has involved the application of Fenton and the photo-Fenton reagents for the treatment of water polluted with diesel oil emulsion [10,16]. Although Fenton reagent has been reported extensively in the literature, there is a scarcity of publications focusing on its use for the treatment of car wash wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of 2 Advances in Environmental Chemistry AOPs include the use of hydrogen peroxide with ultraviolet light (H 2 O 2 /UV) to treat hazardous compounds [7], Fenton and photo-Fenton reagent (H 2 O 2 /Fe 2+ ) [8][9][10], semiconductor photocatalysis [11], and the sonolysis process using ultrasonic irradiation [12]. Among various AOPs, the Fenton reagent is one of the most effective methods for treating various industrial effluents including wastewater [13,14] and oily wastewater [15].…”
Section: Introductionmentioning
confidence: 99%
“…Flotation is investigated as a post-treatment process for the removal of emulsified hydrocarbons and satisfactory results were obtained (4) . On the other hand, Tony et al (5) showed that conventional treatment processes have difficulty in fully removing emulsified oil or small oil droplets. Diffused Air Flotation (DAF) process exhibited remarkable results in removing floatable and suspended materials and it was an effective method to separate oil from aqueous dispersion, chemically treated wastewater, and refinery wastewater (6 ,7) .…”
mentioning
confidence: 99%